Surface current-direct-flow giant magnetoresistance element and its manufacturing method
A laminated structure with Heusler alloys addresses the challenge of achieving high MR ratios and ΔRA in CPP-GMR elements by leveraging controlled film thicknesses, resulting in improved device performance and stability.
Patent Information
- Application Number
- JP2023510698
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-01
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2042-03-01
AI Technical Summary
Existing CPP-GMR elements face challenges in achieving high MR ratios and ΔRA with stable device performance due to variations in ultra-thin insertion layers, particularly in Heusler alloy/NiAl/Ag/NiAl epitaxial structures, and polycrystalline elements with AgSn or AgInZnO spacers.
A laminated structure utilizing Heusler alloys for high spin polarization and asymmetry at the ferromagnetic layer/Heusler alloy interface, with controlled film thicknesses in the nanometer range, is employed to enhance MR ratios and ΔRA, using a ferromagnetic/Heusler alloy/nonmagnetic/Heusler alloy/ferromagnetic stacked structure.
The proposed structure significantly improves MR ratios and ΔRA, achieving stable performance with controlled film thicknesses, reducing variations and enhancing device reliability.
Smart Images

Figure 0007599752000001 
Figure 0007599752000002 
Figure 0007599752000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a current-direct-plane type giant magnetoresistance element and a method for manufacturing the same. [Background technology]
[0002] Current-perpendicular-to-plane giant magnetoresistance (CPP-GMR) elements have attracted attention as a technology for improving the performance of magnetic devices such as magnetic heads for hard disk drives, magnetic sensors, and spin torque oscillators. A basic CPP-GMR element has a structure of a ferromagnetic (FM) layer / non-magnetic (NM) layer / ferromagnetic (FM) layer, and is fabricated by processing this laminated thin film into a pillar shape with a diameter of submicron or less. In the operation of a current-perpendicular-to-plane giant magnetoresistance element, a current is passed through the pillar in a direction perpendicular to the interface in the laminated structure, and the electrical resistance of the laminated structure changes when the relative orientation of the magnetization of the two ferromagnetic layers is parallel or antiparallel.
[0003] To improve the performance of CPP-GMR elements, it is necessary to develop technology to improve the performance indexes, magnetoresistance (MR) ratio and resistance change × pillar area product (ΔRA). When the conventional material CoFe is used as the material for the ferromagnetic layer, the MR ratio is only about 3% [Non-Patent Document 1], which is insufficient for implementation in actual magnetic devices.
[0004] To improve the MR ratio and ΔRA, it is important to select a material system with high spin polarization (β) in the bulk of the ferromagnetic layer and high spin asymmetry (γ) at the interface between the layers. 0.4 Mn 0.6 )Si, Co2Fe(Ga 0.5 Ge 0.5) and other materials) have been applied to the non-magnetic layer, and Ag or AgZn, which has good lattice matching, has been used as the spacer material to develop a (001)-oriented Heusler alloy / Ag (or AgZn) / Heusler alloy epitaxial CPP-GMR element. This element has an MR ratio of 30-60% and a ΔRA of 8-20mΩμm 2 This has been realized [Patent Documents 1-2, Non-Patent Documents 2-4].
[0005] More recently, a CPP-GMR element with a Heusler alloy / NiAl / Ag / NiAl / Heusler alloy epitaxial structure, in which an extremely thin (0.21 nm) NiAl layer was inserted at the Heusler alloy / Ag interface, exhibited a very high MR ratio (82%) and ΔRA (31 mΩμm 2 ) was achieved [Patent Document 3]. This utilizes the high γ at the Heusler alloy / NiAl interface, but there is a problem with the uniformity of the extremely thin insertion layer of 0.21 nm, which causes a problem with the variation in device performance. On the other hand, in more practical polycrystalline magnetoresistance elements, the Heusler alloy Co2Mn 0.6 Fe 0.4 In CPP-GMR elements using Ge and AgSn spacers or AgInZnO precursor spacers, MR ratios of 18% and 54%, respectively, have been observed [Patent Document 4]. However, the latter large MR ratio is brought about by the current confinement structure spacer, and this also has the problem of variation in element performance. Based on these results, new ideas are required to stably achieve large MR ratios and ΔRA with little element variation in both single crystal and polycrystalline devices. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2017-103419 [Patent Document 2] WO2017 / 017978A1 [Patent Document 3] Patent Publication No. 2017-097935 [Patent Document 4] WO2019 / 193871A1 [Non-patent literature]
[0007] [Non-Patent Document 1] S. Yuasa et al., J. Appl. Phys. 92, 2646 (2002) [Non-Patent Document 2] Y. Sakuraba et al., Appl. Phys. Lett. 101, 252408 (2012) [Non-Patent Document 3] S. Li et al., Appl. Phys. Lett. 103, 042405 (2013) [Non-Patent Document 4] Y. Du et al., Appl. Phys. Lett. 107, 112405 (2015) [Non-Patent Document 5] JW Jung et al., Appl. Phys. Lett. 108, 102408 (2016) Summary of the Invention [Problem to be solved by the invention]
[0008] To date, the spin asymmetry (γ) at the ferromagnetic layer / nonmagnetic layer interface has been examined in various combinations. As mentioned above, there is a report of forming a Heusler alloy / NiAl / Ag / NiAl / Heusler alloy epitaxial structure and utilizing the high spin asymmetry (γ) of the Heusler alloy / NiAl to improve the performance of CPP-GMR elements [Non-Patent Document 5]. However, this structure requires control of the thickness of the NiAl insertion layer on the sub-nanometer order, which poses the problem of affecting product yields.
[0009] Therefore, it is desirable to explore a current-direct-plane type giant magnetoresistance element that can utilize high spin polarization (β) and spin asymmetry (γ) at the interface between layers and has a layered structure that allows easy film thickness design. [Means for solving the problem]
[0010] As a result of intensive research into solving the above problems, the inventors came up with the idea that the performance of CPP-GMR elements could be improved by using a layered structure film that utilizes the high spin polarization (β) of the Heusler alloy and the spin asymmetry (γ) at the ferromagnetic layer / Heusler alloy layer interface, and thus completed the present invention.
[0011] [1] The current-direct-plane giant magnetoresistance element of the present invention comprises substrate 11 made of a silicon substrate, an underlayer laminated on substrate 11, first nonmagnetic layers 13a, 13b laminated on the underlayer, and giant magnetoresistance effect layer 17 having at least one laminate layer having lower ferromagnetic layer 14a, lower Heusler alloy layer 14b, second nonmagnetic layer 15, upper Heusler alloy layer 16b, and upper ferromagnetic layer 16a. [2] In the current-direct-plane giant magnetoresistance element [1] of the present invention, the silicon substrate is preferably a Si(001) single crystal substrate. [3] In the current-direct-plane giant magnetoresistance element [1] or [2] of the present invention, the underlayer is preferably made of at least one material selected from the group consisting of Cr, Fe and CoFe. [4] In the current-direct-plane giant magnetoresistance element of the present invention [1] to [3], the underlayer preferably has a thickness of 10 nm or more and less than 200 nm.
[0012] [5] A current-direct-plane giant magnetoresistance element of the present invention, as shown in FIG. 1, for example, comprises a substrate 11 made of MgO, first nonmagnetic layers 13a, 13b laminated on substrate 11, and a giant magnetoresistance effect layer 17 having at least one laminate layer having a lower ferromagnetic layer 14a, a lower Heusler alloy layer 14b, a second nonmagnetic layer 15, an upper Heusler alloy layer 16b, and an upper ferromagnetic layer 16a. [6] In the current-direct-plane giant magnetoresistance element [5] of the present invention, the MgO substrate is preferably a (001) single crystal substrate. [7] In the current-direct-plane type giant magnetoresistance element of the present invention [1] to [6], preferably, the first nonmagnetic layers 13a and 13b are at least one selected from the group consisting of Ag, V, Cr, W, Mo, Au, Pt, Pd, Ta, Ru, Re, Rh, NiO, CoO, TiN, and CuN; the lower ferromagnetic layer is made of Fe, Co, Ni, or a binary or ternary alloy thereof; the lower Heusler alloy layer is a Co-based Heusler alloy; the second nonmagnetic layer is made of at least one material selected from the group consisting of Ag, Cu, Al, AgZn, and AgSn; the upper Heusler alloy layer is a Co-based Heusler alloy; The upper ferromagnetic layer may be made of Fe, Co, Ni, or binary and ternary alloys thereof. [8] In the current-direct-plane type giant magnetoresistance element [7] of the present invention, the Co-based Heusler alloy is preferably represented by the formula Co2YZ, In the formula, Y is preferably at least one selected from the group consisting of Ti, V, Cr, Mn, and Fe, and Z is preferably at least one selected from the group consisting of Al, Si, Ga, Ge, In, and Sn.
[0013] [9] In the current-direct-plane type giant magnetoresistance element of the present invention [1] to [8], preferably, the first nonmagnetic layers 13a and 13b have a thickness of 0.5 nm or more and less than 100 nm; the lower ferromagnetic layer has a thickness of 0.2 nm or more and less than 7 nm; the lower Heusler alloy layer has a thickness of 1.0 nm or more and less than 7 nm; the second nonmagnetic layer has a thickness of 1 nm or more and less than 20 nm; the upper Heusler alloy layer has a thickness of 1.0 nm or more and less than 7 nm; The upper ferromagnetic layer has a thickness of 0.2 nm or more and less than 7 nm, the combined thickness of the lower ferromagnetic layer and the lower Heusler alloy layer is 1.2 nm or more and less than 14 nm; The combined thickness of the upper ferromagnetic layer and the upper Heusler alloy layer is preferably 1.2 nm or more and less than 14 nm.
[10] In the current-direct-plane giant magnetoresistance element of the present invention [1] to [9], preferably, the magnetoresistance ratio is 20% or more and the resistance change area (ΔRA) is 7 mΩμm 2 It would be good if that were the case.
[11] In the current-direct-plane type giant magnetoresistance element of the present invention [1] to
[10] , the giant magnetoresistance effect layer is preferably a single crystal structure having an epitaxial crystal orientation of (001), (110), or (211) in Miller indices indicating the crystal orientation.
[12] In the current-direct-plane type giant magnetoresistance element of the present invention [1] to
[10] , the giant magnetoresistance effect layer preferably has a polycrystalline structure.
[0014]
[13] The device of the present invention uses any one of the current-direct-plane type giant magnetoresistance elements [1] to
[12] .
[14] In the device of the present invention, the device is preferably one of a read head, a magnetic field sensor, a spin electronic circuit, and a tunneling magnetoresistance (TMR) device used on a memory element.
[0015]
[15] A method for manufacturing a current-direct-plane type single-crystal giant magnetoresistance element of the present invention includes the steps of: preparing a silicon substrate; forming a base layer having a single crystal structure on the silicon substrate; forming a film of a first non-ferromagnetic material on the silicon substrate on which the underlayer has been formed, at a substrate temperature of 0° C. or more and 1000° C. or less; forming a giant magnetoresistive layer on the silicon substrate on which the first non-ferromagnetic material has been formed, the giant magnetoresistive layer having at least one laminate layer including a lower ferromagnetic material layer, a lower Heusler alloy layer, a second non-ferromagnetic material layer, an upper Heusler alloy layer, and an upper ferromagnetic material layer; and heat treating the silicon substrate on which the giant magnetoresistive layer has been formed at a temperature of 0° C. or higher and 1000° C. or lower.
[16] A method for manufacturing a current-direct-plane type single-crystal giant magnetoresistance element of the present invention includes the steps of: preparing an MgO substrate; forming a film of a first non-ferromagnetic material on the MgO substrate at a substrate temperature of 0° C. or more and 1000° C. or less; forming a giant magnetoresistive layer on the MgO substrate on which the first non-ferromagnetic material has been formed, the giant magnetoresistive layer having at least one laminate layer including a lower ferromagnetic material layer, a lower Heusler alloy layer, a second non-ferromagnetic material layer, an upper Heusler alloy layer, and an upper ferromagnetic material layer; and heat treating the MgO substrate on which the giant magnetoresistive layer has been formed at a temperature of 0° C. or more and 1000° C. or less.
[0016]
[17] A method for manufacturing a current-direct-plane polycrystalline giant magnetoresistance element of the present invention includes the steps of: preparing a silicon substrate, a glass substrate, an alumina substrate, a germanium substrate, a gallium arsenide substrate, a yttria-stabilized zirconia substrate, or an AlTiC substrate; forming a base layer on the substrate to serve as a polycrystalline electrode; depositing a first non-ferromagnetic material on the substrate on which the underlayer is deposited; forming a giant magnetoresistive layer on the substrate on which the first non-ferromagnetic material has been formed, the giant magnetoresistive layer having at least one laminate layer including a lower ferromagnetic material layer, a lower Heusler alloy layer, a second non-ferromagnetic material layer, an upper Heusler alloy layer, and an upper ferromagnetic material layer; and heat treating the substrate on which the giant magnetoresistive layer is formed at a temperature of 0° C. or more and 500° C. or less. Effect of the Invention
[0017] In the current-direct-plane giant magnetoresistance element of the present invention, in a ferromagnetic / Heusler alloy / nonmagnetic / Heusler alloy / ferromagnetic layered structure, the high spin polarization (β) of the Heusler alloy layer and the high spin asymmetry (γ) at the ferromagnetic layer / Heusler alloy layer interface can improve the MR ratio and ΔRA of the CPP-GMR element. [Brief description of the drawings]
[0018] [Figure 1] 1 is a cross-sectional view of the configuration of a magnetoresistance element having a giant magnetoresistance effect layer according to a first embodiment of the present invention. [Diagram 2] FIG. 1 is a flowchart illustrating a manufacturing method of a magnetoresistance element 10 having a giant magnetoresistance effect layer using a silicon substrate according to a first embodiment of the present invention; (A) is an overall process diagram, and (B) is a detailed diagram of the film formation process of the giant magnetoresistance effect layer. [Diagram 3] FIG. 11 is a flowchart illustrating a method for manufacturing a magnetoresistance element having a giant magnetoresistance effect layer using an MgO substrate according to a second embodiment of the present invention, in which (A) is an overall process diagram, and (B) is a detailed diagram of the film formation process of the giant magnetoresistance effect layer. [Figure 4] 1 is a diagram showing a layered structure of a current-direct-plane type giant magnetoresistance element according to an embodiment of the present invention; [Diagram 5] FIG. 2 is a diagram showing a transmission electron microscope image of a cross section of a main part of a current-direct-plane type giant magnetoresistance element according to one embodiment of the present invention. [Figure 6] FIG. 1 is a diagram showing a CPP-GMR element structure fabricated at a low magnification and a magnetoresistance measurement arrangement according to one embodiment of the present invention. [Figure 7] FIG. 1 is a diagram showing an MR observation curve of a CPP-GMR element structure fabricated at a low magnification, showing one embodiment of the present invention. [Figure 8] 1A and 1B show the characteristics of an embodiment of the present invention, where FIG. 1A is a graph showing the dependency of the MR ratio on the film thickness t, and FIG. 1B is a graph showing the dependency of ΔRA on the film thickness t. [Figure 9] 1 shows one embodiment of the present invention, in which (A) shows the calculation results of the MR ratio when the film thicknesses t=4 nm and t=7 nm, and (B) shows the calculation results of the ΔRA when the film thicknesses t=4 nm and t=7 nm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. 1 is a cross-sectional view of a magnetoresistance element having a giant magnetoresistance effect layer according to a first embodiment of the present invention. In the figure, a magnetoresistance element 10 having a giant magnetoresistance effect layer of this embodiment has a substrate 11, first non-magnetic layers 13a and 13b laminated on the substrate 11, a giant magnetoresistance effect layer 17, and cap layers 18a and 18b. The giant magnetoresistance effect layer 17 has a lower ferromagnetic layer 14a, an upper ferromagnetic layer 16a, and a second nonmagnetic layer 15 provided between the lower ferromagnetic layer 14a and the upper ferromagnetic layer 16a, a first Heusler alloy insertion layer (lower Heusler alloy layer) 14b is provided between the lower ferromagnetic layer 14a and the second nonmagnetic layer 15, and a second Heusler alloy insertion layer (upper Heusler alloy layer) 16b is provided between the upper ferromagnetic layer 16a and the second nonmagnetic layer 15. The total thickness of the lower ferromagnetic layer 14a and the first Heusler alloy insertion layer 14b is selected from the range of 1.2 nm to 14 nm, and the thickness of the first Heusler alloy insertion layer 14b may be adjusted within a range in which the selected total thickness is constant. The total thickness of upper ferromagnetic layer 16a and second Heusler alloy insertion layer 16b is selected from the range of 1.2 nm to 14 nm, and the thickness of second Heusler alloy insertion layer 16b may be adjusted within the range in which the total thickness selected in this manner is constant. Note that first Heusler alloy insertion layer 14b and second Heusler alloy insertion layer 16b may have the same thickness or different thicknesses.
[0020] The substrate 11 may be an MgO substrate or a silicon substrate. When the substrate 11 is a silicon substrate, a general-purpose large-diameter Si substrate, such as 8 inches, may be used. When the substrate 11 is a silicon substrate, an underlayer 12 may be provided between the silicon substrate and the first nonmagnetic layers 13a, 13b. The underlayer 12 may be made of at least one type selected from the group consisting of, for example, NiAl, CoAl, and FeAl. When the substrate 11 is an MgO substrate, it is not necessary to provide the underlayer 12, but it may be provided.
[0021] The first non-magnetic layers 13a and 13b also function as a lower electrode layer and are preferably made of at least one selected from the group consisting of Ag, Cr, Fe, W, Mo, Au, Pt, Pd, Rh, Ta, NiFe, and NiAl. The first non-magnetic layers 13a and 13b may have a two-layer structure of a Cr layer also serving as an underlayer and an Ag layer also serving as a lower electrode layer as in the embodiment, but are not limited thereto and may have a single-layer structure. The first non-magnetic layers 13a and 13b preferably have a film thickness of 0.5 nm or more and less than 100 nm. When the first non-magnetic layers 13a and 13b are less than 100 nm, the surface roughness is less likely to deteriorate, and when the first non-magnetic layers 13a and 13b are 0.5 nm or more, they form a continuous film and are more likely to have the effect of an underlayer, and it is further expected that the magnetoresistance ratio required for this application can be obtained.
[0022] The lower ferromagnetic layer 14a is preferably made of at least one selected from Fe and CoFe. The lower ferromagnetic layer 14a is preferably made to have a thickness of 0.2 nm to 7 nm. If the lower ferromagnetic layer 14a is less than 10 nm, the effect of spin relaxation in the ferromagnetic layer is small, and if it is 0.2 nm or more, it corresponds to the thickness of one atomic layer (ML), which is preferable in that it is easy to form a continuous film. Note that the composition material of the lower ferromagnetic layer 14a does not include a Heusler alloy.
[0023] The first Heusler alloy insertion layer 14b is preferably made of a Co-based Heusler alloy. The first Heusler alloy insertion layer 14b is preferably made to have a thickness of 1.0 nm or more and less than 7 nm. When the thickness is 1.0 nm or more, the contribution of the bulk spin scattering of the Heusler alloy insertion layer is less likely to be small, which is technically more advantageous in that the magnetoresistance ratio is less likely to decrease. When the thickness is less than 7 nm, the influence of spin relaxation is less likely to be large, which is more likely to provide the magnetoresistance ratio required for this application. The Co-based Heusler alloy may be represented by the formula Co2YZ, where Y is at least one selected from the group consisting of Ti, V, Cr, Mn, and Fe, and Z is at least one selected from the group consisting of Al, Si, Ga, Ge, and Sn.
[0024] The second non-magnetic layer 15 is preferably made of at least one selected from the group consisting of Ag, Cu, Al, and AgZn. The second non-magnetic layer 15 is preferably made to have a thickness of 1 nm or more and less than 20 nm. If the thickness of the second non-magnetic layer 15 is less than 20 nm, the effect of spin relaxation in the non-magnetic layer is unlikely to be large, and if the thickness is 1 nm or more, magnetic coupling between the upper ferromagnetic layer 16a and the lower ferromagnetic layer 14a is unlikely to occur, so the relative magnetization angle is unlikely to become small, and it is further expected that the magnetoresistance ratio required for this application can be obtained. The second Heusler alloy insertion layer 16b is preferably made of a Co-based Heusler alloy. The second Heusler alloy insertion layer 16b is preferably made to have a thickness of 1.0 nm or more and less than 7 nm. When the thickness is 1.0 nm or more, the contribution of the bulk spin scattering of the Heusler alloy insertion layer is less likely to be small, which is technically more advantageous in that the magnetoresistance ratio is less likely to decrease. When the thickness is less than 7 nm, the influence of spin relaxation is less likely to be large, which is more likely to provide the magnetoresistance ratio required for this application.
[0025] The upper ferromagnetic layer 16a is preferably made of at least one selected from Fe and CoFe. The upper ferromagnetic layer 16a is preferably made to have a thickness of 0.2 nm or more and less than 7 nm. If the upper ferromagnetic layer 16a is less than 7 nm, the effect of spin relaxation in the ferromagnetic layer is unlikely to be large, and if it is 0.2 nm or more, the thickness corresponds to one ferromagnetic atomic layer (ML), making it easy to form a continuous film. The cap layers 18a and 18b may be made of at least one selected from the group consisting of Ag, Cr, W, Mo, Au, Pt, Pd, Ta, Ru, and Rh. The cap layers 18a and 18b may have a thickness of 1 nm or more and less than 20 nm. The cap layers 18a and 18b may have a two-layer structure of an Ag layer that also serves as an upper electrode layer and a Ru layer that also serves as a protective layer as in the embodiment, but are not limited thereto and may have a single-layer structure.
[0026] Next, a manufacturing process for the device thus configured will be described. 2 is a flow chart for explaining a method for manufacturing a magnetoresistance element 10 having a giant magnetoresistance effect layer using a silicon substrate according to a first embodiment of the present invention, in which (A) is a general process diagram, and (B) is a detailed diagram of a process for forming the giant magnetoresistance effect layer. In FIG. 2(A), a first nonmagnetic material is formed on a silicon substrate 11 at a substrate temperature of 0° C. or more and 1000° C. or less (S100). Next, a giant magnetoresistance effect layer 17 having a lower ferromagnetic material layer 14a, a first Heusler alloy insertion layer (lower Heusler alloy layer) 14b, a second nonmagnetic material layer 15, a second Heusler alloy insertion layer (upper Heusler alloy layer) 16b, and an upper ferromagnetic material layer 16a in this order is formed on the silicon substrate 11 on which the first nonmagnetic material has been formed (S102). In this process, the thicknesses of the first and second Heusler alloy insertion layers 14b and 16b are preferably 1.0 nm or more and less than 7 nm. The lower ferromagnetic layer 14a and the upper ferromagnetic layer 16a preferably have a thickness of 0.2 nm to 7 nm. The giant magnetoresistance effect layer 17 may be a single laminate, or multiple laminates may be provided. Next, cap layers 18a and 18b are formed on the silicon substrate on which the giant magnetoresistance effect layer 17 has been formed. Finally, the silicon substrate on which the giant magnetoresistance effect layer 17 and the cap layers 18a and 18b have been formed is heat-treated as post-annealing at a temperature of 0°C to 1000°C (S104). The post-annealing may be performed in a film forming apparatus before the cap layers 18a and 18b are formed. The heat treatment temperature is preferably 200°C to 600°C.
[0027] Next, the details of the process of forming the giant magnetoresistance effect layer will be described with reference to FIG. 2(B). In the process of forming the giant magnetoresistance effect layer 17, first, the lower ferromagnetic material layer 14 is formed (S122). Next, the first Heusler alloy insertion layer (lower Heusler alloy layer) 14b is formed (S124). Then, the second non-ferromagnetic material layer 15 is formed (S126). Next, the second Heusler alloy insertion layer (upper Heusler alloy layer) 16b is formed (S128). Finally, the upper ferromagnetic material layer 16 is formed (S130). In this way, the formation of the giant magnetoresistance effect layer 17 as a laminate is completed. When a plurality of giant magnetoresistance effect layers 17 are provided, the process of FIG. 2(B) may be appropriately repeated.
[0028] 3 is a flow chart for explaining a method for manufacturing a magnetoresistance element having a giant magnetoresistance effect layer using an MgO substrate according to a second embodiment of the present invention, where (A) is a general process diagram, and (B) is a detailed diagram of the process for depositing the giant magnetoresistance effect layer. In FIG. 3(A), first, the surface of the MgO substrate is cleaned (S200). Next, the MgO substrate is heated and cleaned at a substrate temperature of 300° C. or higher (S202). Then, a first non-ferromagnetic material is deposited on the heated and cleaned MgO substrate at a substrate temperature of 0° C. or higher and 1000° C. or lower (S204). Next, a giant magnetoresistance effect layer 17 having a lower ferromagnetic material layer 14a, a first Heusler alloy insertion layer 14 (lower Heusler alloy layer) b, a second nonmagnetic material layer 15, a second Heusler alloy insertion layer (upper Heusler alloy layer) 16b, and an upper ferromagnetic material layer 16a in this order is formed on the MgO substrate on which the first nonmagnetic material is formed (S206). In this process, the thicknesses of the first and second Heusler alloy insertion layers 14b, 16b are preferably 1.0 nm or more and less than 7 nm. Also, the thicknesses of the lower ferromagnetic material layer 14a and the upper ferromagnetic material layer 16a are preferably 0.2 nm or more and 7 nm or less. The giant magnetoresistance effect layer 17 may be a single laminate or may be provided in multiple layers. Next, cap layers 18a, 18b are formed on the MgO substrate on which the giant magnetoresistance effect layer 17 is formed. Finally, the MgO substrate on which the giant magnetoresistance layer 17 and the cap layers 18a and 18b are formed is heat-treated as post-annealing at a temperature between 0° C. and 1000° C. (S208). The heat treatment temperature is preferably between 200° C. and 600° C.
[0029] Next, the details of the process of forming the giant magnetoresistance effect layer will be described with reference to FIG. 3(B). In the process of forming the giant magnetoresistance effect layer 17, first, the lower ferromagnetic material layer 14 is formed (S222). Next, the first Heusler alloy insertion layer (lower Heusler alloy layer) 14b is formed (S224). Then, the second non-ferromagnetic material layer 15 is formed (S226). Next, the second Heusler alloy insertion layer (upper Heusler alloy layer) 16b is formed (S228). Finally, the upper ferromagnetic material layer 16 is formed (S230). In this way, the formation of the giant magnetoresistance effect layer 17 as a laminate is completed. When a plurality of giant magnetoresistance effect layers 17 are provided, the process of FIG. 3(B) may be appropriately repeated. The present invention will now be described in detail with reference to specific examples, but it should be noted that the present invention is not limited to these examples. EXAMPLES
[0030] As an example, Co 50 Fe 50 / Co2(Fe 0.4 Mn 0.6)Si / Ag / Co2(Fe 0.4 Mn 0.6 )Si / Co 50 Fe 50 We fabricated and measured a CPP-GMR element with an epitaxial layer structure and investigated the Co2(Fe 0.4 Mn 0.6 )Si / Ag / Co2(Fe 0.4 Mn 0.6 The results of the improvement in MR ratio and ΔRA compared to the CPP-GMR element with a Si epitaxial stack structure are shown below. 50 Fe 50 CF, Co2(Fe 0.4 Mn 0.6 )Si will be abbreviated as CFMS.
[0031] Figure 4 shows the layered structure. Specifically, it is MgO(001) substrate / Cr(20nm) / Ag underlayer(80nm) / CF(7-tnm) / CFMS(tnm) / Ag intermediate layer(5nm) / CFMS(tnm) / CF(7-tnm) / Ag cap layer(5nm) / Ru(8nm), and is a single crystal layered film with (001) orientation. Regarding the CFMS film thickness t, structures with t=0 (no CFMS layer), 0.75, 1.5, 3, 4, 5, and 7 (no CF layer) (nm) were fabricated. After deposition of the Ag underlayer, heat treatment was performed at 300℃ for 30 minutes, and after deposition of each CF layer for the sample with t=0nm, and after deposition of each CFMS layer for the other samples, heat treatment was performed at 450℃ for 2 minutes. The transmission electron microscope (TEM) image shown in Figure 5 confirmed the formation of an epitaxial layered structure without atomic diffusion into the Ag intermediate layer or significant unevenness at the layer interface.
[0032] Figure 6 shows a schematic diagram of a CPP-GMR element. The laminated structure of Figure 4 was microfabricated into a pillar shape with a diameter on the order of submicrons. A magnetic field was applied in the in-plane direction of the pillar, and the resistance change was measured using a four-terminal DC configuration. Figure 7 shows a typical MR curve observed at room temperature in a CPP-GMR element with t=4nm. The pillar size was approximately 0.03μm. 2 The resistance of the pillar changes when the magnetization arrangement is parallel or antiparallel. The resistance change amount is ΔR, and the resistance value in the parallel arrangement is R p Let us assume that.
[0033] Figures 8(A) and (B) show the averaged MR ratio and the dependence of ΔRA on t. The MR ratio is calculated by measuring the MR curves shown in Figure 7 for many pillars of various sizes, and extracting the ΔR from the observed MR curves. p ΔRA is the slope of the averaged R p It can be seen that the MR ratio and ΔRA are clearly improved in the structures with t = 3, 4, and 5 nm compared to the structure with t = 7 nm (CFMS / Ag / CFMS laminated structure). In particular, at t = 4 nm, the MR ratio is 49% and the ΔRA is 19 mΩμm 2 For t=7nm (25%, 9mΩμm 2 ) is a significant improvement over
[0034] Figures 9(A) and (B) show the MR ratio and ΔRA at t=4nm and t=7nm calculated based on the theory of spin-dependent transport in CPP-GMR elements [T. Valet and A. Fert, Phys. Rev. B 48, 7099 (1993), N. Strelkov et al., J. Appl. Phys. 94, 3278 (2003)]. The value (0.97) obtained by theoretical calculation of band matching is used for γ at the CF / CFMS interface. The calculation results also show that both are clearly improved at t=4nm.
[0035] The above results demonstrate that the ferromagnetic / Heusler alloy / nonmagnetic / Heusler alloy / ferromagnetic layered structure is effective in improving the MR ratio and ΔRA, i.e., in improving the performance of CPP-GMR elements, and that film thickness control to realize this function is possible on the nanometer order.
[0036] In the embodiment of the present invention, the case where a single crystal CPP-GMR element is manufactured has been mainly described, but the present invention is not limited to this, and the same effect can be obtained not only with single crystal but also with polycrystal CPP-GMR elements. Also, although the case where an Ag layer is used as the nonmagnetic intermediate layer of the CPP-GMR element is shown, the present invention is not limited to this, and as mentioned above, a general-purpose nonmagnetic metal layer such as a Cu layer or an Al layer may also be used. [Industrial Applicability]
[0037] The magnetoresistance element of the present invention is a giant magnetoresistance element using a Heusler alloy that has the excellent magnetoresistance characteristics required for application to practical devices such as read heads of magnetic hard disks, and is suitable for use in practical devices such as magnetic heads, magnetic field sensors, spin electronic circuits, and tunnel magnetoresistance devices. [Explanation of symbols]
[0038] 11 Silicon substrate, MgO substrate 12 Base layer 13, 13a, 13b First non-magnetic layer (lower electrode layer) 14a Lower ferromagnetic layer 14b Heusler alloy intercalation layer (lower Heusler alloy layer) 15 Second non-magnetic layer 16b Heusler alloy intercalation layer (upper Heusler alloy layer) 16a Upper ferromagnetic layer 17 Giant magnetoresistance layer 18a, 18b cap layer
Claims
1. A substrate made of a silicon substrate; A base layer laminated on the substrate; a first nonmagnetic layer laminated on the underlayer; a giant magnetoresistive layer having at least one laminate layer including a lower ferromagnetic layer, a lower Heusler alloy layer, a second non-magnetic layer, an upper Heusler alloy layer, and an upper ferromagnetic layer; A surface-direct current type giant magnetoresistance element comprising: the silicon substrate is a Si(001) single crystal substrate; The underlayer is made of at least one material selected from the group consisting of Cr, Fe and CoFe.
2. 2. The current-direct-to-surface giant magnetoresistance element according to claim 1, wherein the underlayer has a thickness of 10 nm or more and less than 200 nm.
3. the first nonmagnetic layer is at least one selected from the group consisting of Ag, Cr, Fe, W, Mo, Au, Pt, Pd, Rh, Ta, NiFe, and NiAl; the lower ferromagnetic layer is made of at least one material selected from Fe and CoFe, the lower Heusler alloy layer is a Co-based Heusler alloy; the second nonmagnetic layer is made of at least one selected from the group consisting of Ag, Cu, Al, and AgZn; the upper Heusler alloy layer is a Co-based Heusler alloy; 3. The current-direct-to-surface giant magnetoresistance element according to claim 1, wherein said upper ferromagnetic layer is made of at least one material selected from the group consisting of Fe and CoFe.
4. The Co-based Heusler alloy has the formula Co 2 It is represented as YZ and 4. The current-direct-surface giant magnetoresistance element according to claim 3, wherein, in the formula, Y is at least one selected from the group consisting of Ti, V, Cr, Mn, and Fe, and Z is at least one selected from the group consisting of Al, Si, Ga, Ge, and Sn.
5. the first nonmagnetic layer has a thickness of 0.5 nm or more and less than 100 nm; the lower ferromagnetic layer has a thickness of 0.2 nm or more and less than 7 nm; the lower Heusler alloy layer has a thickness of 1.0 nm or more and less than 7 nm; the second nonmagnetic layer has a thickness of 1 nm or more and less than 20 nm; the upper Heusler alloy layer has a thickness of 1.0 nm or more and less than 7 nm; The upper ferromagnetic layer has a thickness of 0.2 nm or more and less than 7 nm, the combined thickness of the lower ferromagnetic layer and the lower Heusler alloy layer is 1.2 nm or more and less than 14 nm; 5. The current-direct-plane giant magnetoresistance element according to claim 1, wherein the total thickness of said upper ferromagnetic layer and said upper Heusler alloy layer is 1.2 nm or more and less than 14 nm.
6. The magnetoresistance ratio is 20% or more, Resistance change area product (ΔRA) is 7 mΩμm 2 6. The current-direct-plane giant magnetoresistance element according to claim 1, wherein
7. 7. The current-direct-to-plane giant magnetoresistance element according to claim 1, wherein the giant magnetoresistance effect layer has a single crystal structure having an epitaxial crystal orientation of (001), (110), or (211) in Miller indices indicating crystal directions.
8. 7. The current-direct-to-plane giant magnetoresistance element according to claim 1, wherein said giant magnetoresistance effect layer has a polycrystalline structure.
9. A device using the current-direct-plane giant magnetoresistance element according to any one of claims 1 to 8.
10. 10. The device of claim 9, wherein the device is one of a read head, a magnetic field sensor, a spin electronic circuit, and a tunneling magnetoresistance (TMR) device used on a storage element.
Citation Information
Patent Citations
Magnetoresistance effect element for laminating heuslar magnetic layer and non-magnetic intermediate layer in body-centered cubic structure and magnetic head
JP2004146480A
Magnetoresistance element, use and production method for the same, and method for producing heusler alloy
JP2017027647A
Magnetoresistive element, and manufacturing method and method of application of the same
JP2017097935A
Single crystal magnetoresistive element, method for manufacturing the same, and method for using the same
JP2017103419A
Current perpendicular to plane magnetoresistive sensor employing half metal alloys for improved sensor performance
US20140335377A1
